Partitioning of fresh crude oil between floating, dispersed and sediment phases: Effect of exposure order to dispersant and granular materials. (15th June 2016) - Boglaienko, Daria; Tansel, Berrin
Abstract: When three or more high and low energy substrates are mixed, wetting order can significantly affect the behavior of the mixture. We analyzed the phase distribution of fresh floating Louisiana crude oil into dispersed, settled and floating phases depending on the exposure sequence to Corexit 9500A (dispersant) and granular materials. In the experiments artificial sea water at salinity 34‰ was used. Limestone (2.00–0.300 mm) and quartz sand (0.300–0.075 mm) were used as the natural granular materials. Dispersant Corexit 9500A increased the amount of dispersed oil up to 33.76 ± 7.04%. Addition of granular materials after the dispersant increased dispersion of oil to 47.96 ± 1.96%. When solid particles were applied on the floating oil before the dispersant, oil was captured as oil-particle aggregates and removed from the floating layer. However, dispersant addition led to partial release of the captured oil, removing it from the aggregated form to the dispersed and floating phases. There was no visible oil aggregation with the granular materials when quartz or limestone was at the bottom of the flask before the addition of oil and dispersant. The results show that granular materials can be effective when applied from the surface for aggregating or dispersing oil. However, the granular materials in the sediments are not effective neither for aggregating nor dispersing floating oil. Graphical abstract: Highlights: Phase distribution of crude oil in float, dispersed, and solid material was studied. Fresh crude oil was exposed to dispersant and granular materials. Oil dispersion improved when granular materials were added after dispersant. Majority of floating oil sank with granular materials when no dispersant was used. Granular materials added before oil and dispersant did not aggregate with oil.